A Review of: Mlambo, Obert Bernard 2022. Land Expropriation in Ancient Rome and Contemporary Zimbabwe: Veterans, Masculinity and War. London: Bloomsbury. - Matei-Popescu, Florian (Pnyx: Journal of Classical Studies, 2025)
Review of: Mlambo, Obert Bernard 2022. Land Expropriation in Ancient Rome and Contemporary Zimbabwe: Veterans, Masculinity and War. London: Bloomsbury.